Using a transcriptomic approach to understand poor growth performance in farmed orange‐spotted grouper ( Epinephelus coioides ) larvae: a case study in a commercial hatchery - Su Khi Ng; Cher Chien Lau; Min Pau Tan; Siti Azizah Mohd Nor; Muhd Danish‐Daniel; Nor Afiqah‐Aleng; Zainal Abidin Muchlisin; Nur Fadli (New Zealand Journal of Marine and Freshwater Research, 2024)
The orange‐spotted grouper ( Epinephelus coioides ) is one of the most popular fish in aquaculture due to its high economic value. However, the random occurrence of slow‐growing population has led to profit loss. Therefore, transcriptomic analysis was performed to identify the molecular mechanisms involved in driving slow and fast growth, towards addressing this issue. Results show that low expression of developmental genes such as bone morphogenetic protein 1 ( BMP 1 ) and somatostatin ( SST ), as well as GH/IGF axis‐related genes ( IGF‐1 , IGF2 , IGFBP1 , IGFBP2 ) and its downstream signalling pathways are correlated with the metabolism and digestive‐system‐related pathways in slow‐growing groupers. Enrichment analysis further revealed that cellular process and biological regulation, as well as several pathways including glycolysis/gluconeogenesis, linoleic acid metabolism, protein digestion and absorption, and cholesterol metabolism were differentially expressed in slow‐growing groups. The findings implied that the genomic architecture of growth between the different families raised and the likely problem of inbreeding have led to significantly reduced growth. It is also suggested that better husbandry practices (optimal dietary requirement) is also vital in supporting the success of a genetic improvement programme. These findings recommend growth improvement of orange‐spotted groupers via molecular monitoring and artificial selection, complemented by specific dietary feeding.